LACK OF AWARENESS OR GENUINE EMERGENCY: A SURVEY TO FIND REASONS OF GYNAECOLOGY / OBSTETRICS PATIENTS VISITING OPD DURING PANDEMIC; ARE YOU IGNORANT OR ARE YOU IGNORING - Urooj, Uzma; Khan, Sumaira; Siraj, Asifa; Mushtaq, Rubina (Pakistan Armed Forces Medical Journal, 2020)
Objectives: To explore the reasons of Gynaecology/Obstetrics patients visiting OPD’s and awareness regarding basic care and risks associated with unnecessary visits to hospital, during COVID-19 Pandemic Study Design: Cross sectional quantitative survey. Place and Duration of Study: Pak Emirates Military Hospital, Gynaecology/Obstetrics OPD during month of May. Methodology: A questionnaire exploring reasons of OPD visit of Gynaecology/Obstetrics patients during COVID-19 pandemic and lockdown by government. Results: Results will be calculated by using SPSS-22. Conclusion: This study showed that despite of awareness of mode of transmission of disease, most of the patients used public transport to reach the hospital for routine checkups. This study pointed out the gaps in awareness, specific aspects of knowledge, seriousness of situation, invariably guiding aim of future awareness and educational campaigns. This will lead to increased awareness of people regarding the seriousness of the disease and preventing rapid transmission of the disease by taking proper protective measures.